Prevention of Lung Pathology and Mortality in Rabbit Staphylococcus aureus Pneumonia with Cytotoxin-Neutralizing Monoclonal IgGs that Penetrate Epithelial Lining Fluid. (4th October 2017) - Stulik, Lukas; Rouha, Harald; Labrousse, Delphine; Visram, Zehra; Nagy, Gabor; Croisier, Delphine; Nagy, Eszter
Abstract: Background: Pneumonia caused by Staphylococcus aureus, irrespective of antibiotic resistance, is associated with high mortality. Six cytolytic toxins produced by S. aureus, namely alpha-hemolysin (Hla) and the five bi-component leukocidins, are important for pneumonia pathogenesis of both MRSA and MSSA. We previously described two human IgG1 monoclonal antibodies (mAb), ASN-1 and ASN-2 that together (ASN100) neutralize these six toxins. Unlike rodents, rabbits are sensitive to all these cytotoxins and we therefore tested ASN100 for prophylactic efficacy in dose-ranging studies in stringent rabbit models of S. aureus pneumonia. Methods: Male New Zealand White rabbits were intravenously immunized with ASN100 (0.08 to 20 mg/kg, 24 hours prior to intratracheal instillation of either USA300 CA-MRSA, USA100 HA-MRSA or MSSA strains. Survival was monitored for up to 156 hours post challenge. Alternatively gross necropsy, lung histopathology, and microbiological analyses were performed at 12 hours post challenge. MAb concentrations were determined in serum and bronchoalveolar lavage fluid (BALF) by ELISA. Results: Control animals succumbed to infection within 24 hours irrespective of the S. aureus challenge strain. ASN100 at 20 mg/kg was fully protective against all five S. aureus strains tested. Lower doses resulted in different protection levels in a challenge strain-dependent manner. Lung pathology and bacterial load showed ASN100 dose-dependent improvements in the USA300 CA-MRSA model. Animals protected by ASN100 cleared the infection within 2 to 3 days. Pharmacokinetic analyses of ASN100 in BALF from naïve and S. aureus infected animals confirmed efficient penetration into lung epithelial lining fluid (ELF), reaching protective levels by 24 hours and peak concentrations by 48 hours post-dosing. Conclusion: Our data demonstrate that the IgG1 mAbs of ASN100 rapidly penetrate the lung and reach high local concentrations at the mucosal surfaces. Cytotoxin-neutralization prevents lethal S. aureus pneumonia and significantly improves the lung pathology in rabbits. ASN100 is currently being studied in a Phase 2 trial for the prevention of pneumonia in mechanically-ventilated patients whose lower airways are heavily colonized by S. aureus. Disclosures: L. Stulik, Arsanis: Employee and Shareholder, Salary; H. Rouha, Arsanis: Employee and Shareholder, Salary; D. Labrousse, Vivexia: Employee, Salary; Z. Visram, Arsanis: Employee and Shareholder, Salary; G. Nagy, Arsanis: Employee and Shareholder, Salary; D. Croisier, Vivexia: Employee and Shareholder, Salary;  E. Nagy, Arsanis: Employee and Shareholder, Salary